The Effect of Task-Based Language Instruction on Shambu Secondary Students’ Speaking Self-Efficacy Beliefs and Benefits - Dheressa, Moti Alemayehu; Olana, Tamiru; Bekele, Ebisa (JOLLT Journal of Languages and Language Teaching, 2023)
TBLT represents an approach to language learning that prioritizes meaning but does not neglect form. It emphasizes the importance of engaging students’ natural abilities to acquire language incidentally as they engage with language as a meaning-making tool. This study attempts to explore the effects of TBLI on Shambu Secondary School students’ speaking self-efficacy beliefs in speaking skills performances during the intervention training if improve or not the studentsâ€™ speaking self efficacy beliefs. To this end, two intact classes were selected in Shambu Secondary School using mixed method research. The treatment group went through twelve week teaching program, whereas the comparison group received the usual conventional instruction. The data were gathered from speaking self efficacy questionnaires and analyzed by using ANCOVA and content analysis was used to analyze the interview data. The results of the quantitative analysis revealed that TBLI increased the studentsâ€™ English speaking self efficacy beliefs in the areas of their speaking performances. Moreover, the findings of the interview disclosed several themes about the merits of TBLI on studentsâ€™ self-efficacy in speaking skills performance showing positive responses from the treatment groups. At the end, a range of implications is suggested for the different stakeholders.Â